2017
DOI: 10.1063/1.5000507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total emitted electron velocity distribution function on the plasma sheath near a floating wall

Abstract: Electrons emitted from a solid surface can noticeably affect characteristics of plasma sheath surrounding that surface by modifying current balance at wall, charge separation in sheath region and Bohm criterion at sheath edge. We establish a static sheath model with kinetic electrons and cold ions to emphasize the effect of different total emitted electron velocity distribution functions (EEVDFs) on classic sheath solution and its structure transition. Four total EEVDFs with same average energy are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…For secondary electrons, similarly one can consider its velocity distribution function, see Qing's work for details [41] . Note that when half Maxwellian distribution is selected, when its temperature 𝑇 𝑠𝑒 approaches 0, the solution converges to a fluid model solution, which utilizes energy conservation, flux conservation and secondary emission coefficient as shown in Eq.…”
Section: ⅲ Theoretical Analysesmentioning
confidence: 99%
“…For secondary electrons, similarly one can consider its velocity distribution function, see Qing's work for details [41] . Note that when half Maxwellian distribution is selected, when its temperature 𝑇 𝑠𝑒 approaches 0, the solution converges to a fluid model solution, which utilizes energy conservation, flux conservation and secondary emission coefficient as shown in Eq.…”
Section: ⅲ Theoretical Analysesmentioning
confidence: 99%
“…The choice of distribution function for emitted secondary electrons is not unique, and can influence particle as well as energy fluxes especially in the vicinity of boundaries [70,71]. Here it is chosen as half-Maxwellian, which was also adopted in several previous studies [63,69,72,73]:…”
Section: Kinetic Effects Of Ion-surface Interactionmentioning
confidence: 99%
“…(2013, 2014) found that the critical SCL sheath has a solution if the temperature ratio of plasma electrons to emitted electrons is no less than unity. Qing & Hu (2017) found that different assumptions of the total emitted electron velocity distribution (EEVD) can significantly affect the range of average energy ratio of emitted electrons to primary electrons, in which the critical SCL sheath has a solution. This then indicates that the classic sheath may transit to an inverse sheath structure when the ratio is out of the range.…”
Section: Introductionmentioning
confidence: 99%